2022
DOI: 10.1155/2022/2539519
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Alleviates Skeletal Muscle Insulin Resistance by Downregulating Long Noncoding RNA

Abstract: Long noncoding RNA (lncRNA) is a crucial factor in the progression of insulin resistance (IR). Resveratrol (RSV) exhibits promising therapeutic potential for IR. However, there are few studies on whether RSV improves IR through lncRNA. This study aimed to determine whether RSV could influence the expression of lncRNA and to elucidate the underlying mechanism. Mice were divided into three groups: control group, high-fat diet (HFD) group, and HFD + RSV group. We conducted a high-throughput sequencing analysis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It was reported that RES inhibited cancer cell survival, while the knockdown of lncRNA H19 resulted in increased sensitivity to RES therapy ( 38 ). Liu et al ( 20 ) showed that RES could promote skeletal muscle insulin resistance via a competitive endogenous RNA (lncRNA NONMMUT044897.2/miR-7051-5p/SOCS1 pathway). In addition, RES inhibits cell apoptosis by suppressing lncRNA XLOC_014869 in lung injury rats ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that RES inhibited cancer cell survival, while the knockdown of lncRNA H19 resulted in increased sensitivity to RES therapy ( 38 ). Liu et al ( 20 ) showed that RES could promote skeletal muscle insulin resistance via a competitive endogenous RNA (lncRNA NONMMUT044897.2/miR-7051-5p/SOCS1 pathway). In addition, RES inhibits cell apoptosis by suppressing lncRNA XLOC_014869 in lung injury rats ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there are a substantial number of literature about RES, including a few studies that have involved the differential effects of polyphenols such as RES on lncRNA expression. Interestingly, a study established that RES alleviates skeletal muscle insulin resistance by downregulating lncRNA ( 20 ), and inhibits cell apoptosis by suppressing lncRNA in rats' lungs ( 21 ). However, the effects of different RES concentrations on apoptosis-related lncRNA and mRNA functions in POGCs have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The control mice were fed a routine diet, while the IR mice were fed a 60% high-fat diet (HFD) for 8 weeks to induce IR. The IR model was validated by determining the area under the curve in accordance with the protocol presented in our previously published study 26 . Insulin resistance was estimated using the quantitative insulin sensitivity check index (QUICKI).The mice were anesthetized, and their hepatic tissues were removed.…”
Section: Methodsmentioning
confidence: 99%
“…LncRNA PTGS2 can impair pancreatic β-cell function by regulating miR-146a-5p and upregulating RBP4, an effect that is reversible ( 118 ). And reversal of abnormal lncRNAs can also reverse skeletal muscle IR, such as in the case of lncRNA NONMMUT044897.2 ( 119 ). These evidences demonstrated that lncRNAs are located upstream of miRNAs in the regulation of many types of DM and that their use as biomarkers for clinical diagnosis of DM or as potential therapeutic targets is valid and feasible ( Table 2 ).…”
Section: Ncrnas In Diabetesmentioning
confidence: 99%